(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The paper provides a comparative study of the current economic context of operational costs in commercial banks and the theoretical scholars ’ view of operational costs. The classification of the costs of the Commercial Bank is covered, the composition and dynamics of the costs are analyzed and practical recommendations for their optimization are given. The analysis of the ravages of scientists, the opinions that are against each other, is coming. Also mentioned is the operational status of operational costs of some commercial banks and the future plans, strategic plans.